Korelasi Keterampilan Memahami Teks Laporan Hasil Observasi dengan Keterampilan Menulis Teks Laporan Hasil Observasi Siswa Kelas X SMK Negeri 1 Lembah Gumanti - Yani, Yosi Andre; Arief, Ermawati (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this study is (1) to describe the skills of understanding the text of the observation report of class X SMK Negeri 1 Lembah Gumanti , (2) describe the writing skills of the observation report text of class X SMK Negeri 1 Lembah Gumanti , and (3) analyze the correlation of understanding skills text of the report on the results of observation with the skill of writing a report text as a result of observation of class X students of SMK Negeri 1 Gumanti Valley. This type of research is quantitative research with descriptive methods. The design of this study is correlational. There are three conclusions in this study. First, the skill of understanding the text of the report on the observation results of class X students of SMK Negeri 1 Lembah Gumanti is in more than enough qualifications with a value of 74.57. Second, the text writing skills of the report on the results of observation of class X students of SMK Negeri 1 Lembah Gumanti are in good qualifications with a value of 76.56. Third, the skill of understanding the text of the observation report has a significant correlation with the writing skills of the report's observation text in class X of SMK Negeri 1 Lembah Gumanti at 85%.Â Kata Kunci: Korelasi, Memahami, Menulis, Teks Laporan Hasil Observasi